Molecular Determinants of in vitro Plant Regeneration: Prospects for Enhanced Manipulation of Lettuce (Lactuca sativa L.) - Bull, Tawni; Michelmore, Richard (Frontiers in Plant Science, 2022)
In vitro plant regeneration involves dedifferentiation and molecular reprogramming of cells in order to regenerate whole organs. Plant regeneration can occur via two pathways, de novo organogenesis and somatic embryogenesis. Both pathways involve intricate molecular mechanisms and crosstalk between auxin and cytokinin signaling. Molecular determinants of both pathways have been studied in detail in model species, but little is known about the molecular mechanisms controlling de novo shoot organogenesis in lettuce. This review covers our current knowledge on molecular determinants of de novo organogenesis and shoot embryogenesis as well as provides insight into applying this information for enhanced in vitro regeneration in other species such as lettuce (Lactuca sativa L.).